Development of Cut Chrysanthemum (Chrysanthemum morifolium Ramat.) production in substrate culture under restricted root volume - Viyachai, Taweesak (2015)
The effects of three different substrate volumes (34, 73, 140 cm3) and three different substrates (coconut peat 100 %, burnt rice husk 100 % and coconut peat+burnt rice husk 50:50) grown at 64 plant/m2 were investigated. Plant height and the total leaf area of chrysanthemums reduced significantly when substrate volume decreased regardless of substrate type but chrysanthemum grown in substrate volume of 140 cm3 being produced at the highest plant height. Chrysanthemums grown in a substrate volume of 140 cm3 had the largest root surface area. The relative water content and macro elements in leaves did not differ significantly between treatments. Chrysanthemums grown in restricted root volume had high proline levels throughout growth period. Root:shoot ratio did not differ between treatments. Plants grown in substrate volume of 140 ml showed the highest number of flower of 17.79 and flower diameter of 20.82 cm. The effects of two substrate volumes (73 and 140 cm3) and three irrigation frequencies (4, 6, 8 times/day) were investigated to determine a suitable irrigation frequency for the growth and flowering of cut chrysanthemum grown under restricted root volume. There was interaction between irrigation frequency and substrate volume on plant height of chrysanthemum. The tallest plant of 109.25 cm was obtained from chrysanthemum, grown at 140 cm3 irrigated 6 times/day. Chrysanthemum irrigated 6 and 8 times/day had significantly higher phosphorus content in leaf than being irrigated 4 times/day. The total dry weight of chrysanthemum irrigated 6 and 8 times/day was higher than 4 times/day 32% and 23% consequently. Chrysanthemum irrigated 8 times per day had the highest number of flower,indicated at 20.44. In conclusion, chrysanthemum grown in substrate volume of 140 cm3 had better growth and flower quality than in 73 cm3. The growth and flowering of chrysanthemum irrigated 6 and 8 times/day were better than 4 times/day. The effects of two chrysanthemum varieties (‘New White’ and ‘New Yellow’) and three different plant densities (64, 81 and 99 plants/m2) were investigated to determine a suitable plant density for the growth and flowering to determine financial possibility. For instance, the plant grown at 81 plants/m2 had higher leaf area index than at 64 plants/m2. The pedicel length of plant density of 99 plants/m2 was longer than of 64 plant/m2 18.33% and the stem fresh weight and total dry weight did not differ between three plant densities. Plant densities also did not significantly affect photosynthesis rate, transpiration rate, stomatal conductance, and Fv/Fm. Other than that, chrysanthemum grown at 99 plants/m2 had the highest plant height but at the same time did not significantly differ from other two plant densities. Plant densities did not significantly affect the day of flowering, the number of flower, flower diameter, inflorescence diameter, flower color and vase life. These results indicated that under root restriction, chrysanthemum could be grown at high plant densities up to 99 plants/m2. From the gross profit analysis, chrysanthemum ‘New White’ and ‘New Yellow’ grown at 81 plants/m2 provided highest margin. The last experiment investigated the growth and flowering, perception of growers, distributors and consumer and financial feasibility of chrysanthemum cultivated in the tray and the trough system. Furthermore, the growth and flowering of chrysanthemum produced in the tray system almost did not differ from the trough system. However, the yield of chrysanthemum produced in the trough system was higher than of the tray system significantly. Besides that, the quality of chrysanthemum produced in the tray and the trough system received very good scores from growers, distributors and consumers in almost all characteristics. From the gross profit analysis, the tray system had higher profit than the trough system but both of them were lower than that of soil-based system.